Efficacy and Safety of Colesevelam in Combination with Pioglitazone in Patients with Type 2 Diabetes Mellitus - Rosenstock, J.; Truitt, K. E.; Baz-Hecht, M.; Ford, D. M.; Tao, B.; Chou, H. S. (Hormone and Metabolic Research, 2014)
Colesevelam improves glycemic control in patients with type 2 diabetes when added to existing metformin-, sulfonylurea-, or insulin-based regimens. We evaluated colesevelam’s effects in subjects on stable pioglitazone-based therapy. This 24-week multicenter, double-blind, randomized, placebo-controlled study enrolled adults with type 2 diabetes who had suboptimal glycemic control [HbA1c≥58 mmol/mol (7.5%) and ≤ 80 mmol/mol (9.5%)] on pioglitazone (30 or 45 mg) with or without 1–2 other oral antidiabetes medications. Subjects were randomized to colesevelam 3.8 g/day (n=280) or placebo (n=282) added to existing pioglitazone-based therapy. Primary efficacy variable was mean change in HbA1c from baseline to Week 24. Secondary variables included safety and tolerability, fasting plasma glucose changes, glycemic responses, and lipid profile. Tertiary variables included lipid particle profile changes by nuclear magnetic resonance. Colesevelam decreased HbA1c [least-squares mean treatment difference, − 3.5 mmol/mol (− 0.32%); p<0.001] and fasting plasma glucose (− 14.7 mg/dl; p<0.001) vs. placebo at Week 24. More subjects receiving colesevelam vs. placebo achieved HbA1c reduction ≥ 7.7 mmol/mol (0.7%) (40% vs. 25%; p<0.001) or HbA1c<53 mmol/mol (7.0%) (21% vs. 13%; p=0.012). Colesevelam also decreased total cholesterol (mean treatment difference, − 6.5%), LDL-cholesterol (− 16.4%), non-HDL-cholesterol (− 9.8%), apolipoprotein B (− 8.8%), and total LDL particle concentration, and increased apolipoprotein A1 (+3.4%) and triglycerides (median treatment difference, + 11.3%) vs. placebo (all p<0.001). There were no serious drug-related adverse events, and the majority of adverse events were mild or moderate. In subjects with type 2 diabetes inadequately controlled with pioglitazone-based therapy, add-on colesevelam therapy improved glycemic control and lipid parameters and was well tolerated. ClinicalTrials.gov identifier: NCT00789750.
Keywords: bile acid sequestrants; cholesterol; glycemic control; glucose; thiazolidinediones; type 2 diabetes mellitus